2020
DOI: 10.1002/art.41417
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis Pathogenesis, Prediction, and Prevention: An Emerging Paradigm Shift

Abstract: Rheumatoid arthritis (RA) is currently diagnosed and treated when an individual presents with signs and symptoms of inflammatory arthritis (IA) as well as other features, such as autoantibodies and/or imaging findings, that provide sufficient confidence that the individual has RA‐like IA (e.g., meeting established classification criteria) that warrants therapeutic intervention. However, it is now known that there is a stage of seropositive RA during which circulating biomarkers and other factors (e.g., joint s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 78 publications
1
92
0
2
Order By: Relevance
“…The region of interest (ROI) in this study is indicated in the open black circle. (C) As illustrated, arthritis-induced joint pathology was assessed in this study, including cartilage, bone erosion, and osteoclast number (1,4), pannus formation (2), synovitis and cellular infiltration (3,5). The density of sympathetic nerves was evaluated using the ratelimiting enzyme for norepinephrine synthesis, tyrosine hydroxylase, as a marker for these nerves.…”
Section: Animal Sacrifice and Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The region of interest (ROI) in this study is indicated in the open black circle. (C) As illustrated, arthritis-induced joint pathology was assessed in this study, including cartilage, bone erosion, and osteoclast number (1,4), pannus formation (2), synovitis and cellular infiltration (3,5). The density of sympathetic nerves was evaluated using the ratelimiting enzyme for norepinephrine synthesis, tyrosine hydroxylase, as a marker for these nerves.…”
Section: Animal Sacrifice and Tissue Preparationmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) afflicts about 1% of adults worldwide. RA is a debilitating chronic inflammatory autoimmune disease of the joints, with no cure and no strategy for prevention (1). In RA, inflammation, immune cell infiltration into the synovium of affected joints and circulating proinflammatory cytokines are characteristic features of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although not necessarily required for the development of RA, autoAbs can readily be found many years before the onset of symptomatic disease in the evolution model of RA [ 107 , 108 , 109 ]. During the presymptomatic phase of the disease, B cells undergo a series of selection, expansion, epitope spreading and antibody maturation processes [ 22 , 29 ], providing physicians an opportunity for early detection and prevention of the disease.…”
Section: Predictive Values Of Rf Acpa and Anti-carp Ab In The Diamentioning
confidence: 99%
“…To effectively utilize the huge data sets that can now be generated through autoantibody and other biomarker analytics, machine learning and artificial intelligence (AI) in the setting of precision health (PH) are major drivers for biomarker use in clinical practice (2,(4)(5)(6). For example, autoantibodies combined with other multi-analyte "omic" profiles are now beginning to form the basis of predicting disease thus allowing for disease prevention strategies and earlier and effective personalized interventions for established disease (7)(8)(9)(10). As medical intervention continues to move toward disease prediction and a model of "intent to PREVENT" morbidity and mortality (11), futuristic diagnostics will take into consideration symptoms and risks, as opposed to an established disease and organ involvement approach.…”
Section: Overviewmentioning
confidence: 99%